2016
DOI: 10.1177/1757743816651896
|View full text |Cite
|
Sign up to set email alerts
|

The realities of being young, unemployed and poor in post-industrial Britain

Abstract: Poverty is a complex cultural phenomenon that is very much in existence in contemporary Post-Industrial Britain. A young person's poverty struck situation, in addition to their marginalised hierarchal position shapes their repetitive life cycle comprising of different but inter-related forms of marginality. The young people in this ethnographic study were found to experience marginalisation in their education, training and work spheres, as well as in their community, family and home. The purpose of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In other words, alongside an ‘unreflexive commitment’, there was an unreflexive response that did not dispute the authority or correctness of the school or its teachers. Russell (2016), in a discussion on unemployed young people, discussed a similar scenario. She found that the subjects in her study, like the poorer students in this research, did not reject societal norms, but had to ‘negotiate domineering structures that position them as unemployed, lazy and welfare-dependant’ (Russell, 2016:165).…”
Section: Findings and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In other words, alongside an ‘unreflexive commitment’, there was an unreflexive response that did not dispute the authority or correctness of the school or its teachers. Russell (2016), in a discussion on unemployed young people, discussed a similar scenario. She found that the subjects in her study, like the poorer students in this research, did not reject societal norms, but had to ‘negotiate domineering structures that position them as unemployed, lazy and welfare-dependant’ (Russell, 2016:165).…”
Section: Findings and Discussionmentioning
confidence: 93%
“…Russell (2016), in a discussion on unemployed young people, discussed a similar scenario. She found that the subjects in her study, like the poorer students in this research, did not reject societal norms, but had to ‘negotiate domineering structures that position them as unemployed, lazy and welfare-dependant’ (Russell, 2016:165). However, while the young adults felt that these labels did not apply to them, they frequently applied them to others in a similar position.…”
Section: Findings and Discussionmentioning
confidence: 93%
“…Burgess et al, 2003; Selenko and Pils, 2016). An unsuccessful transition may be compounded by a lack of pathways into employment for the long-term unemployed (Beck, 2017; Russell, 2016). Recent trends also suggest a narrowing in the opportunity for young people to move into their first employment (Murphy and Oesch, 2017).…”
Section: Scarringmentioning
confidence: 99%
“…NEETs often experience financial hardship, a loss of self-esteem and status, and a range of psycho-social distress and disorders including depression and anxiety, which then negatively affect relationships with family and friends. In an ethnographic study of NEETs, Russell found that ‘feelings of marginalisation across work, home and education’ (2016: 172) were widespread among participants. Moreover, being NEET has long-term negative consequences, increasing the likelihood of lower wages and unemployment later on.…”
Section: The ‘Neet Problem’mentioning
confidence: 99%